Language Style Used in the Business Articles of Suitmedia’s Website - Jessica Patricia; Ivonne Muliawati Harsono (Institute of Research and Community Outreach - Petra Christian University, 2023)
The objective of the study was to identify the different types of language style that were used in two business articles. The writer analyzed the language style used in the strategy and creative article published on the Suitmedia website in October 2022. The study used Keraf's (2010) theory of language style based on diction, which utilizes three indicators: vocabulary, sentence length, and sentence structure. Moeliono et al.'s (2017) theory of inversion and Chaer's (2014) theory of syntax were also used as supporting theories. This study was conducted using a descriptive qualitative approach. The data analysis showed that the strategy article used the formal language style, and the creative article used the informal language style. The research findings indicated three differences in language style between strategy and creative articles, which are vocabulary, sentence structure, and sentence length.